Actitudes profesionales docentes y su relación con las Actitudes de Aprendizaje de los alumnos del cuarto al sexto grado de la Institución Educativa Nº 00537 "Matilde del Águila Velásquez" del distrito de Rioja, 2006 - Tuesta Chavarry, Harrison (2006)
The human attitude is a form of social motivation that predisposes the action(share) of an individual towards certain aims(lenses), designates the orientation of the deepest dispositions(regulations) of the human being before an aim(lens), hereby the human being is forming(training) his(her,your) personality. The educational attitudes in the field of the process of education learning, it(he,she) has to see with one of the aspects regarding the perspective of good or bad(wrong) teachers, to realize an effective class or not it(he,she) is like that, that to educate the children, activity that the condition(state) entrusts the teachers, the attitude of the last ones, from the conception of way of operating with regard to the process of education learning, has much that to see in the formation(training) of attitudes towards the learning that the children have. From this perspective the investigation(research) has been projected one orientated to achieve the aim(lens) that consists of determining the relation that exists between(among) the professional attitudes of the teachers and the attitudes towards the learning of the students of the quarter(room) to the sixth degree of the Educational lnstitution N ° 00537 "Matilde Del Águila Velazques" of the district of Rioja, in the year 2006. Whose(which) hypothesis to verifying went that it(he,she) exists a directly proportional relation between(among) the professional attitudes of the teachers and the attitudes towards the learning of the students of the quarter(room) to the sixth degree of the Educational lnstitution N º 00537 " Matilde Del Águila Velazques ", of the district of Rioja, in the year 2006. The information was gathered of 8 teachers to gather information about the professional attitude and 207 students to gather information about the attitudes towards the learning; both to the teachers and to the students he(she) administered a questionnaire by means of the technology(skill) of the questionnaire. Whose(which) information was tried by means of the coefficient of Pearson's correlation. The values that one has found to allowed to establish them following: The coefficient of equal Pearson to - 0,15 means that an inversely proportional relation exists between(among) the professional educational attitude democratically and the attitudes towards the learning of the students of the quarter(room) to the sixth degree of the Educational lnstitution N º 00537 "Matilde Del Águila Velazques", of the district of Rioja, in the year 2006. The coefficient of equal Pearson to 0,14 means that a directly proportional relation exists between(among) the professional educational attitude authoritarian and the attitudes towards the learning of the students of the quarter(room) to the sixth degree of the Educational lnstitution N ° 00537 "Matilde Del Águila Velazques ", of the district of Rioja, in the year 2006. The coefficient of equal Pearson to-O, 15 means that an inversely proportional relation exists between(among) the professional educational attitude permissive and the attitudes towards the learning of the students of the quarter(room) to the sixth degree of the Educational lnstitution N ° 00537 " Matilde Del Águila Velazques ", of the district of Rioja, in the year 2006.